EKSPLORASI SIKAP KEMANDIRIAN SISWA MELALUI EKSTRAKURIKULER PRAMUKA DI SEKOLAH DASAR - Fadhilah, Dian Ayu Nur; Rachmadtullah, Reza (Jurnal Pendidikan Dasar, 2025)
Abstract: This study aims to determine the role of scouting extracurricular activities in implementing an attitude of independence in students. This study uses a qualitative research method. The methods used are implementing various activities such as pioneering, breaking scout codes, camping, competitions, and so on, and there are factors from the role of teachers/scout leaders, peers, and parents. The implementation of the character of independence through scouting extracurricular activities in Elementary Schools has been carried out well. This is evidenced by the behavior of students who have implemented the values ​​of independence such as being able to carry out tasks as well as possible, being able to carry out tasks independently, having a self-confident attitude and also being able to concentrate in the learning process. Keywords: Scouting Extracurricular, Independence Attitude, Elementary School